2021
DOI: 10.3325/cmj.2021.62.68
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of human papillomavirus genotypes in women with high-grade cervical intraepithelial lesions and cervical carcinoma and analysis of human papillomavirus-16 genomic variants

Abstract: Aim To analyze the distribution of high-risk human papillomavirus (HR-HPV) genotypes and the diversity of HPV-16 genomic variants in Croatian women with high-grade squamous intraepithelial lesions (HSIL) and cervical carcinoma. Methods Tissue biopsy specimens were obtained from 324 women with histopathologically confirmed HSIL or cervical carcinoma, 5 women with low-grade SIL, and 49 women with negative histopathology. HR-HPV DNA was detected with Ampliquality HPV-type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 37 publications
(9 reference statements)
1
3
1
Order By: Relevance
“…We found an increased incidence of multiple HPV infections in women with cervical dysplasia compared to those without dysplasia (31.1 and 22.6%, respectively); however, there was no association between multiple infections and dysplasia. This is supported by results from other studies [22,30,35]. In both the study and control groups, single infection was more common than multiple infections, but a different prevalence may be observed by expanding the spectrum of HR-HPV genotypes and testing for genotypes that are uncommon or have low oncogenic potential.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…We found an increased incidence of multiple HPV infections in women with cervical dysplasia compared to those without dysplasia (31.1 and 22.6%, respectively); however, there was no association between multiple infections and dysplasia. This is supported by results from other studies [22,30,35]. In both the study and control groups, single infection was more common than multiple infections, but a different prevalence may be observed by expanding the spectrum of HR-HPV genotypes and testing for genotypes that are uncommon or have low oncogenic potential.…”
Section: Discussionsupporting
confidence: 85%
“…Other studies have shown that HPV 31 was one of the most common HR genotypes. As in Montenegro, HPV 31 was the third most common genotype in Serbia [18] and Bulgaria (10.7 and 12.2%, respectively) [16]; however, in Croatia [30], Bosnia and Herzegovina [22], and Kosovo [19] it was the second most common genotype (12.6, 14.3, and 15.4%, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…8 A recent study on Croatian women confirmed that HPV16, mainly belonging to the European branch, was most frequently associated with histologically confirmed high-grade intraepithelial lesions (CIN2 or CIN3) and cervical cancer. 28 In the present study, the lineage A of HPV16 was the most frequently detected lineage, and although it was associated with high-grade lesions (CIN2/CIN3), we could not demonstrate a difference between these high-grade lesions and cervical cancer. Another study conducted in a different region in Brazil also found a high prevalence of the lineage A of HPV16 in samples of high-and low-grade lesions, including cervical cancer.…”
Section: Discussioncontrasting
confidence: 81%
“…A recent study on Croatian women confirmed that HPV16, mainly belonging to the European branch, was most frequently associated with histologically confirmed high-grade intraepithelial lesions (CIN2 or CIN3) and cervical cancer. 28…”
Section: Discussionmentioning
confidence: 99%
“…A recent study with women in Croatia con rms the predominance of HPV-16, mainly belonging to the European branch, as the most frequently associated with histologically con rmed HSIL and cervical cancer [29].…”
Section: Discussionmentioning
confidence: 97%